2011
DOI: 10.1177/070674371105600305
|View full text |Cite
|
Sign up to set email alerts
|

Assertive Community Treatment in the Netherlands: Outcome and Model Fidelity

Abstract: Our evidence supports the importance of model fidelity for improving patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
(31 reference statements)
0
40
1
2
Order By: Relevance
“…In fact, the level of illness severity observed in our study is even more pronounced than that found with similar instruments in national [18] and international [19] samples of patients with psychoses. In the study of Parabiaghi et al [18], carried out in 2003 in nine communities mental health services in Italy, a large cohort of 2059 patients was monitored over a one-year period.…”
Section: Discussioncontrasting
confidence: 53%
“…In fact, the level of illness severity observed in our study is even more pronounced than that found with similar instruments in national [18] and international [19] samples of patients with psychoses. In the study of Parabiaghi et al [18], carried out in 2003 in nine communities mental health services in Italy, a large cohort of 2059 patients was monitored over a one-year period.…”
Section: Discussioncontrasting
confidence: 53%
“…Explanations for the lack of results were sought in lack of experience of the teams (Killaspy et al 2006) and the fact that standard care incorporated many elements that are characteristic of ACT (Killaspy et al 2006; Sytema et al 2007). Another Dutch study found a (negative) relationship between level of ACT model fidelity, especially team structure, and some items of the HoNOS and the number of homeless days (Van Vugt et al 2011). Implementation of fully fledged ACT is especially difficult in rural areas because of the low population density, the lack of adequate services for patients and the lack of personnel (Meyer and Morrissey 2007).…”
Section: Introduction: Act and Flexible Actmentioning
confidence: 99%
“…H. McGrew, Bond, Dietzen, & Salyers, 1994;McGuire et al, in press; McHugo, Drake, Teague, & Xie, 1999;van Vugt et al, 2011). Fidelity monitoring is a critical tool for providing developmental feedback, either in program start-up for learning program principles and practices or as an important component in supporting the long-term sustainability of such practices (Bond et al, 2014).…”
mentioning
confidence: 99%